Empowering Students: Integrating Moderate Values in Islamic Education through Project-Based Learning - Bachrul Ulum; Dian Septi Nur Afifah (Jurnal Pendidikan Agama Islam Indonesia (JPAII), 2025)
Purpose of the study: This study aims to highlight the important role of Islamic Religious Education in shaping moderate religious character among students, as well as to explore the integration of moderate religious values and the application of Project-Based Learning (PjBL) in the Islamic Religious Education curriculum at Bhinneka PGRI University, Indonesia. Methodology: The methodology used was a qualitative approach with a case study design, involving 50 students from various study programmes who took Islamic Religious Education courses. Data were collected through in-depth interviews, observations, and document analysis, which were then comprehensively analysed. Main Findings: The results showed that the implementation of PjBL significantly improved the understanding and application of moderation values through collaborative interaction and practical involvement in social projects. In addition, PjBL also served as an effective tool in strengthening attitudes of tolerance and inclusiveness among students. Novelty/Originality of this study: This study offers an innovative approach to the development of the IRE curriculum, integrating religious moderation values through the PjBL methodology. These findings make an important contribution to educational institutions in creating a moderate and socially responsible younger generation in the digital age.